A quantitative environmental impact assessment of Australian ultra-processed beverages and impact reduction scenarios - Kim Anastasiou; Michalis Hadjikakou; Ozge Geyik; Gilly A. Hendrie; Phillip Baker; Richard Pinter; Mark Lawrence (Public Health Nutrition)
Abstract